Strategies for Improving the Brightness of Aggregation‐Induced Emission Materials at Aggregate Level. Issue 10 (22nd March 2023) - Gui, Yixiong; Chen, Keyao; Sun, Yan; Tan, Yonghong; Luo, Wenshuai; Zhu, Dongxia; Xiong, Yu; Yan, Dingyuan; Wang, Dong; Tang, Ben Zhong
Comprehensive Summary: The brightness of fluorescent agents directly determines the imaging performance as required. Among various fluorophores, small organic species are promising given its exact purity/composition and excellent processibility. However, chromophores with planar geometry may suffer from the undesirable aggregation‐caused quenching (ACQ) phenomenon. Encouragingly, luminogens showing aggregation‐induced emission (AIE) features are preferable as the aggregates which are the most common used state. In this review, we mainly focus on the strategies employed for boosting the brightness of AIE‐active luminogens (AIEgens). From molecule to morphology levels, approaches that regulate electronic transition processes of the molecule or the packing extent of aggregates in order to confine molecular motion, reduce π‐π stacking, disrupt fluorophore‐water interactions, etc ., are presented. In the end, the current challenges and perspectives are briefly discussed. We anticipate that this review will stimulate new insights and more efforts for the advancement of ultrabright AIEgens. Abstract :